Effectuation 10 Year Waypoint - Read, Stuart; Dolmans, Sharon (Senate Hall, 2012)
As a concept, effectuation celebrated its tenth birthday in 2011. We use the milestone to look back at the work done to date and to look forward to new questions and issues. What we see is an idea that has added shape to the conversation regarding entrepreneurship. By offering a clear theoretical and testable perspective, effectuation has enabled both a foundation for supporting work as well as criticism. The resulting dialog has advanced our level of understanding regarding the phenomenon of entrepreneurship, and in the process it has opened exciting specific questions and entirely new directions. By inventorying as much current work and as many future questions as we could identify, we seek to encourage the interaction, and look forward to what will be created by effectuation's twentieth birthday. Keywords: effectuation; entrepreneurship; uncertainty; theory; review; venture
Keywords: effectuation|entrepreneurship|uncertainty|theory|review|venture